Study on milling periods on the iron mill scale particle size and properties - Ruhiyuddin, Mohd Zaki; Faizul, Che Pa; Murizam, Darus; A. R. M., Nazri (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/